The Influence of the Talking stickLearning Method on the Language Skills of Children Aged 5-6 Years - Eka Damayanti; Ahmad Syukri Sitorus (Jurnal Raudhah, 2026)
This study aimed to examine the effect of the talking stick learning method on the language skills of children aged 5–6 years at TK IT Bunayya 7 Laut Dendang. This study employed a quantitative approach using a quasi-experimental design involving 40 children. Data were collected through observation and analyzed using SPSS through normality, homogeneity, and independent t-tests. The results showed that the data were normally distributed and homogeneous. Hypothesis testing indicated that the  talking stick learning method had a significant effect on the language skills of children aged 5–6 years. The novelty of this study lies in providing empirical evidence that the talking stick learning method creates structured opportunities for children to actively participate in learning, communicate their ideas, and improve their language skills in an early childhood education setting. Therefore, the talking stick learning method can be considered an effective instructional strategy for enhancing young children's language development.